2014
DOI: 10.5455/msm.2014.26.335-338
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rotavirus Diarrhea in Hospitalized Children in Kosovo

Abstract: Background:Diarrhea is a leading cause of child mortality worldwide. Rotavirus is one of the most common causes of severe diarrhea and dehydration in children. Authors reviewed epidemiological and clinical data of the rotavirus diarrhea in Kosovo.Methods:This is a prospective study carried between January 1st and December 31st 2011. All data, comprising demographics, nutrition, clinical presentation, laboratory findings, management and outcome of the rotavirus diarrhea are collected on the specially designed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Fever was observed in 32.5% of the subjects, which is almost similar to the findings in hospital studies of 43.96%–44%. [ 24 25 ] The majority of the children in our study did not show any sign of dehydration (75%). The degree of dehydration was proven to have no correlation with being positive for rotavirus in this study ( P = 0.227), which is different from the result of a previous study that demonstrated a significant association between the degree of dehydration and rotavirus diarrhea.…”
Section: Discussionmentioning
confidence: 69%
“…Fever was observed in 32.5% of the subjects, which is almost similar to the findings in hospital studies of 43.96%–44%. [ 24 25 ] The majority of the children in our study did not show any sign of dehydration (75%). The degree of dehydration was proven to have no correlation with being positive for rotavirus in this study ( P = 0.227), which is different from the result of a previous study that demonstrated a significant association between the degree of dehydration and rotavirus diarrhea.…”
Section: Discussionmentioning
confidence: 69%
“…Different result was also shown by a study in Nepal that 67.5% children with RV infection were males. The relationship between incidence of RV infection and sex group is still unknown until now (Shariff et al, 2003;Ansari et al, 2013;Ismaili-Jaha et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1 Diarrhea is defined as watery bowel movements more than four times a day, with mucus and blood and not. 2 Diarrheal disease is a disease that requires immediate remedial action because it can lead to fatalities if delayed, thus Drug very important role in health care, especially diarrhea. Various options are currently available drugs that required careful consideration in choosing a drug.…”
Section: Introductionmentioning
confidence: 99%